Impact of Early Clinical Exposure in improving knowledge among 1st year M.B.B.S. Students of Government Medical College, Baramulla - Berjina Farooq Naqshi, Syed Mubashir, AdilBashir,Lubna Rashid (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Early clinical exposure acting as a big link between clinical and non clinical set ups, setting upas vital and interesting teaching method, exposes students very early to the clinical set up.This pattern of teaching has been used by medical colleges worldwide to narrow